hiteboard Notes Tracking Erasing System - Khader Abu Madi; Mohammed Yahya; Sami Abu Asbe; Shukri Ghanim (My University, 2015)
mounted on its edges and suitable software can be developed to overcome this challenge. The software will use a condition; if the camera detected one blob the software distinguishes it is writing process by the smart pen. If the camera detected four blobs the software distinguishes it is erasing process.  The erasing part can be developed to be more flexible, compact, suitable, and adaptable with any board. Also, there are a lot of ideas and accessories that may develop the project and make it more attractive and professional.